2018
DOI: 10.1016/j.ijppaw.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterisation of Acanthocephala in pinnipedia of the North and Baltic Seas

Abstract: Harbour seals (Phoca vitulina) and grey seals (Halichoerus grypus) are final hosts of acanthocephalans in the German North and Baltic Seas. Parasitic infections in seals can cause pathological changes, which may result in deteriorated health of the host. Common gastrointestinal parasites of harbour and grey seals are acanthocephalans and a number of 275 of 2460 (11.2%) investigated seals from 1996 to 2013 were infected with Corynosoma spp. (Acanthocephala, Polymorphidae). The prevalence showed a wave-like patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
(70 reference statements)
1
18
0
Order By: Relevance
“…García-Varela et al (2005) concluded that the Corynosoma species found in the Caspian Sea is C. caspicum and not C. strumosum. Indeed, C. strumosum from the land-locked Caspian seal recorded by Amin et al 2011 was characterised with proboscis hooks and trunk spines distinct from other Northern European morphological descriptions (Nickol et al 2002, Waindok et al 2018, Leidenberger et al 2019), suggesting that they may not be conspecific. Surprisingly, Corynosoma caspicum Golvan and Mokhayer, 1973, described based on immature specimens from sturgeons in Caspian Sea (Golvan and Mokhayer 1973) and often found in three-spined stickleback (Gasterosteus aculeatus) (Niksirat et al 2006), has not yet been reported in Pusa caspica or another definitive host.…”
Section: Zoogeographymentioning
confidence: 77%
See 4 more Smart Citations
“…García-Varela et al (2005) concluded that the Corynosoma species found in the Caspian Sea is C. caspicum and not C. strumosum. Indeed, C. strumosum from the land-locked Caspian seal recorded by Amin et al 2011 was characterised with proboscis hooks and trunk spines distinct from other Northern European morphological descriptions (Nickol et al 2002, Waindok et al 2018, Leidenberger et al 2019), suggesting that they may not be conspecific. Surprisingly, Corynosoma caspicum Golvan and Mokhayer, 1973, described based on immature specimens from sturgeons in Caspian Sea (Golvan and Mokhayer 1973) and often found in three-spined stickleback (Gasterosteus aculeatus) (Niksirat et al 2006), has not yet been reported in Pusa caspica or another definitive host.…”
Section: Zoogeographymentioning
confidence: 77%
“…By contrast, C. semerme has a circumpolar distribution, having been reported from the Arctic Ocean, north Atlantic and north Pacific (e.g. Popov and Fortunato 1987, Kaimoto et al 2018, Waindok et al 2018 (Fig. 2).…”
Section: Zoogeographymentioning
confidence: 83%
See 3 more Smart Citations